The Location-Based Tax Incentives in Indonesia: Special Economic Zones - Afida, Chabibah Nur; Widodo, Cahyo Aji (JURNAL PAJAK INDONESIA, 2023)
Tax incentive policies can be seen as a two-sided coin that has costs and benefits. Many countries adopt location-based policies to address economic disparities between regions in their countries. This essay will discuss the implementation of location-based tax incentives in the form of Special Economic Zones (SEZs) in Indonesia. This paper examines the relevant literature and provisions underlying location-based tax incentives, particularly special economic zones (KEK). SEZ development in Indonesia began in 2009 with the aim of attracting investment, spurring economic growth, and contributing to economic development in the region and the country. However, after more than a decade of its launching, SEZs in Indonesia have not developed optimally. Several problems discourage investors from investing in SEZs, such as infrastructure and land acquisition. Fiscal incentives provided in SEZs are also not very effective in attracting investors.